Construction and characterisation of a heparan sulphate heptasaccharide microarray. Issue 10 (20th January 2017) - Yang, Jianhong; Hsieh, Po-Hung; Liu, Xinyue; Zhou, Wen; Zhang, Xing; Zhao, Jing; Xu, Yongmei; Zhang, Fuming; Linhardt, Robert J.; Liu, Jian
Abstract : A targeted heptasaccharide library was synthesised to prepare a heparan sulphate (HS) microarray. Abstract : A targeted heptasaccharide library was synthesised to prepare a heparan sulphate (HS) microarray. The array was probed with two glycan-binding proteins, HS 3- O -sulphotransferase1 and antithrombin, demonstrating the binding selectivity between HS and proteins. The HS microarray technique will accelerate the understanding of the structure and function relationships of HS.